PENGARUH PENERAPAN MODUL PETUALANGAN BODASTA TERHADAP PERILAKU ANTI KORUPSI SISWA SD DI KELURAHAN KEDUNGGALENG PROBOLINGGO - Helga Graciani Hidajat; Muhammad Wildan Hidayat; Faradila Sabrina (Jurnal PGSD Musi, 2018)
The purpose of this research is explore the effect of “Petualangan Bodasta Modul” through anti-corruption behavior in primary student at Kedunggaleng Probolinggo. This research is kuantitative research with experimental design. Participants in this research are 42 students of grade 4 in Kedunggaleng City, Probolinggo. Participants is separated into 2 groups (21 students in experimental group and 21 students in control group. Instrument of this research is quesionner about responsibility behavior as one of symptom of anti corruption behavior. This instrument has validated by expert in primary school education. Difference test shows that sig. (2-tailed) in experiment group 0,000< 0,05, Hnuul is rejected and Hi is received, so “Petualangan Bodasta Modul” can increase anti corruption behavior.